Synovial Sarcoma of the Extremities. A Diagnosis that is easily missed - Pan, K.L.; Chan, W.H; Premsenthil, M.; S., Haniza (Malaysian Orthopaedic Journal, 2009)
Synovial sarcoma of the extremities is an uncommon type of soft tissue sarcoma occurring predominantly in young adults at the para-articular regions. We present a series of 10 patients with an average age of 44 years and include a follow-up of 39 months. Eight patients had a surgical procedure for a mistaken benign lesion. In contrast to other soft tissue sarcomas, the swellings were associated with pain and most were fixed to the underlying structures. Five patients had a local recurrence after many years, stressing the necessity for close and long term follow-up in these patients.